Give me an Easy Topic, Please: My Experience of Supervising Theses - Karn, Sajan Kumar (Journal of NELTA, 2010)
Thesis writing is demanding in that it requires a great deal of time, patience, study, creativity, writing proficiency and also critical and analytical expertise on the part of researchers. Unfortunately, many of the beginners do not seem to understand the gravity of such a high level academic feat and consequently pose a lot of problems for thesis supervisors, guidance committee, university department, etc. This paper endeavors to scrutinize students' misconceptions and negligence against depth and requisites of the thesis writing. Besides this, it also tries to specify the expected responsibilities of supervisors and researchers. This largely draws on my experience and inferences obtained while supervising M. Ed. (English) theses, unstructured interview (conversation) with the students/researchers, a close examination of thesis drafts, and interactions with colleagues (thesis supervisors). Key words: Research, plagiarism,research problem, thesis writing DOI: 10.3126/nelta.v14i1.3092 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 63-70